Characteristics of two-phase flow patterns of non-Newtonian fluid xanthan gum-nitrogen in a horizontal square microchannel at high temperature - Ahmad Yusuf Ramadhan; Haslinda Kusumaningsih; Deendarliyanto (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
The development of microfluidic systems in the microscale requires a deep understanding of the characteristics of two-phase flow, especially when involving non-Newtonian fluids such as Xanthan Gum (XG) solution. This study aims to examine the flow patterns, transitions between patterns, and frictional pressure drop in two-phase flows of XG-Nitrogen and Aquades-Nitrogen in a square-shaped horizontal microchannel at high temperatures. The methods used include an experimental approach with high-speed camera visualization and pressure measurements, as well as numerical analysis using a two-phase pressure drop prediction model. The experimental results show three main flow patterns, namely slug, churn, and slug-annular, with the absence of bubbly and wavy-annular patterns in the XG flow, indicating the strong influence of non-Newtonian viscosity. The flow pattern transition occurs with increasing gas flow rate, causing changes in the slug shape. The evaluation of the prediction model shows better accuracy in 0.2% XG solution compared to Aquades, although there is still a deviation at high values. This study confirms the importance of non-Newtonian fluid viscosity on flow stability and frictional stress, and contributes to the design of more efficient microcooling systems